Study on Development and Improvement of Government Hospital Service System in Ministry of Public Health by Using Information Technology - จันทวิบูลย์ อัมพร; ทระเทพ ชาญวิทย์ (Journal of Preventive Medicine Association of Thailand, 2019)
Study on Development and Improvement of Government Hospital Service System in Ministry of Public Health by Using Information Technology, is a Quantitative Research aims to analyze capacity, opportunity, and readiness of factors related to information technology (IT) using in hospitals of the Ministry of Public Health, and to provide suggestion for improvement of hospital service system by using IT. Three factors of capacity and readiness were used for improvement. They were 1) people-ware factor which included criteria to rate knowledge and capacity of IT-men and users; 2) hardware factor and internet networking system which included adequacy and management ability i.e. problem solving, having backup system by rating according to severity of problem, ability to solve problems, and category of mainframe, personal computers and software using in the system; and 3) factors on hospital IT system/program i.e. number and type of system, ability to develop and maintain the system, and ability to solve problems. IT was used to improve appointment system of hospitals in the project. User satisfaction evaluation was also done. Result of the study revealed that hospitals under the Ministry of Public Health have capacity to use IT to develop various systems. According to readiness of hospitals and categorization of hospitals for capacity development, the results showed problems of hospitals personnel lack of knowledge on data information, IT networking, safety and HIS system. Suggestions are there should be manpower plan, especially on IT man, users in hospital in terms of number, capacity, knowledge and paradigm to accommodate needs of people on time, fit their life style, and use new methods of working by using IT, increasing efficiency of work (effective and fast), reducing redundant of work process and time to reduce cost in the future. Policy recommendations were systematically and continuously integration of development and improvement of service system of hospital under the Ministry of Public Health with planning on development of IT system. The effective implementation would occur from high level policy mandate and large amount of budget to support. Development and Improvement of Government Hospital Service System in Ministry of Public Health by Using Information Technology may start in some system such as appointment system. Implementation would do in hospitals that are in the same group such as specialized hospital, hospitals within the same department, or hospitals in the same health region because they are in the same management system. Success in the small points will be combined to be a big success that could be connected together in the future.